2004
DOI: 10.1080/14659890410001711715
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with attendance for first appointments at an alcohol clinic and the effects of telephone prompting

Abstract: Aims: To identify variables associated with response to first appointments at a specialist alcohol treatment clinic, and to determine the effect on patients' attendance of a brief telephone prompt prior to the appointment. Design, participants and intervention: Multivariate analysis of patient characteristics from referral letters and aspects of the quality of the referral process was carried out. Consecutive non-repliers (n~100), non-attenders (n~100) and attenders (n~100) were studied. A further 100 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 26 publications
4
47
0
Order By: Relevance
“…In contrast, a study of attendance at a specialist alcohol treatment centre in the UK 89 undertook multivariate analysis of patient characteristics of non-repliers (n = 100), non-attenders (n = 100) and attenders (n = 100) and found no statistically significant association between source of referral and attendance. A study in a paediatric dermatology clinic in Hong Kong 122 found that non-attendance was significantly higher among referrals from the emergency department than among referrals by private practitioners (p = 0.05).…”
Section: Patterns and Influences On Health-care Attendance Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, a study of attendance at a specialist alcohol treatment centre in the UK 89 undertook multivariate analysis of patient characteristics of non-repliers (n = 100), non-attenders (n = 100) and attenders (n = 100) and found no statistically significant association between source of referral and attendance. A study in a paediatric dermatology clinic in Hong Kong 122 found that non-attendance was significantly higher among referrals from the emergency department than among referrals by private practitioners (p = 0.05).…”
Section: Patterns and Influences On Health-care Attendance Behaviourmentioning
confidence: 99%
“…In addition, limited and inconsistent evidence was yielded on the effect of source of appointment on attendance behaviour. Just two UK papers 89,121 reviewed included quantitative analyses addressing this hypothesised relationship and these related to contrasting settings and employed inconsistent categorisation of sources.…”
Section: The Source Of the Original Appointmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15][16] Studies in primary care and specialty clinics have demonstrated that staff phone calls are an effective intervention for reducing no-shows. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] However, this convincing work is difficult to apply, because staff phone calls are timeconsuming and costly. Moreover, while this intervention is thought to be cost effective in clinics with high baseline noshow rates, the efficacy is less clear when baseline no-show rates are low.…”
Section: Introductionmentioning
confidence: 99%
“…18,19,30,31 Nevertheless, even in practices with low baseline no-show rates, the risk of no-show is heterogeneous-that is, some patients are more likely of noshows than others. 9,10,28,29,[32][33][34] Prior work has effectively demonstrated that no-shows are predictable; validated models can accurately predict the likelihood that a patient will fail to keep a scheduled appointment. 9,[35][36][37][38] Subspecialty clinics have made use of the predictability of no-shows by integrating predictive modeling to target interventions to those at high risk of no-show.…”
Section: Introductionmentioning
confidence: 99%